First‐trimester ductus venosus velocity ratio as a marker of major cardiac defects. (3rd May 2019) - Wagner, P.; Eberle, K.; Sonek, J.; Berg, C.; Gembruch, U.; Hoopmann, M.; Prodan, N.; Kagan, K. O.
ABSTRACT: Objectives: To examine ductus venosus (DV) flow in fetuses with and those without a cardiac defect and to evaluate different phases of DV flow in addition to the standard assessment of DV pulsatility index for veins (PIV) and the a‐wave. Methods: This was a retrospective study of singleton pregnancies that underwent first‐trimester ultrasound screening, which included DV flow assessment, at the University of Tübingen (between 2010 and 2017) or the University of Cologne (between 2013 and 2016). The study population comprised normal fetuses and fetuses with major cardiac defects at a ratio of 10:1. For each fetus, the following parameters of the DV waveform were evaluated: qualitative assessment of the a‐wave, PIV measurement and ratios of flow velocities during the S‐wave (S) or D‐wave (D) and the a‐wave (a) or v‐wave (v). Reproducibility of DV‐PIV and DV flow ratios was evaluated in 30 fetuses in which the DV flow was assessed twice. Results: Our study population included 480 anatomically normal fetuses and 48 with a cardiac defect. Median fetal nuchal translucency (NT) in the normal and in the affected group was 1.9 mm and 2.6 mm, respectively. In five (1.0%) of the normal and 18 (37.5%) of the affected cases, fetal NT thickness was above the 99 th centile. In the normal group, the DV a‐wave was reversed in 15 (3.1%) cases and the DV‐PIV was above the 95 th centile in 25 (5.2%). In the cases with cardiac defects, the a‐wave was reversed and the DV‐PIV measurement was above the 95 th centile in 26 (54.2%). The reproducibility of measurement of the ratios of DV flow velocities was similar to that of the DV‐PIV. Most cardiac defects were associated with an abnormal a/S or a/D ratio. If the cut‐off for these two ratios was set at the 5 th centile of the normal distribution, the detection rate of fetal cardiac anomalies would be 62.5%. This compares favorably with the DV‐PIV, which detects 26 (54.2%) of the affected fetuses for the same threshold. Conclusion: In the first trimester, the a/S ratio has the potential to detect approximately 60% of congenital cardiac defects for a false‐positive rate of 5%. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd.